POPULATION OF GASTROINTESTINAL NEMATODE IN GALLUS GALLUS DOMESTICUS AT BEED, MAHARASHTRA - SHINDE, L.V.; DESHMUKH, S.B.; GORE, G.D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
The present paper deals with the population study of nematode parasites in Gallus Gallus domasticus, 70% fowl of Beed District were found affected by nematode parasites. The species identified were Acaridae galli and Hetrakis gallinae.